Vice-Chancellor visits laboratories - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Mohamad Najib, Mohammad Nor (Penerbit UMP, 2008)
Sept 2, Gambang: The Faculty of industrial Sciences and Technology (FIST) will be acquiring its own teaching and research laboratories within the year.